Accelerometers data interoperability - easing interactive applications development - Carvalho, Jorge Rodrigues; Manzato, Marcelo Garcia; Goularte, Rudinei (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Research in Natural Interfaces, sub-area of Ubiquitous Computing, investigates the use of non-traditional devices to support user interaction with applications in less intrusive ways (gestures, voice and writing based on electronic ink, for instance). With the increasing popularity of accelerometers, developers now have another tool that can be used to provide interaction between users and different applications, such as interactive TV environments. However, applications that make use of accelerometers are currently being developed for specific situations, and their implementations and handled documents are also dependent on the domain for which they were designed. This paper aims to propose a model to formalize how the accelerometer data may be handled in a generic way. In addition, the model enables the description of rules to aggregate value to these data through the addition of meanings. This is done by proposing a layered architecture to structure and share data in a flexible way. An example of use and the description of a simple application that makes use of the proposed model are also presented.